Efficacy and safety of maralixibat treatment in patients with Alagille syndrome and cholestatic pruritus (ICONIC): a randomised phase 2 study - Gonzales, Emmanuel; Hardikar, Winita; Stormon, Michael; Baker, Alastair; Hierro, Loreto; Gliwicz, Dorota; Lacaille, Florence; Lachaux, Alain; Sturm, Ekkehard; Setchell, Kenneth D R; Kennedy, Ciara; Dorenbaum, Alejandro; et al. (The Lancet (British edition), 2021)
Alagille syndrome is a rare genetic disease that often presents with severe cholestasis and pruritus. There are no approved drugs for management. Maralixibat, an apical, sodium-dependent, bile acid transport inhibitor, prevents enterohepatic bile acid recirculation. We evaluated the safety and efficacy of maralixibat for children with cholestasis in Alagille syndrome. ICONIC was a placebo-controlled, randomised withdrawal period (RWD), phase 2b study with open-label extension in children (aged 1–18 years) with Alagille syndrome (NCT02160782). Eligible participants had more than three times the normal serum bile acid (sBA) levels and intractable pruritus. After 18 weeks of maralixibat 380 μg/kg once per day, participants were randomly assigned (1:1) to continue maralixibat or receive placebo for 4 weeks. Subsequently, all participants received open-label maralixibat until week 48. During the long-term extension (204 weeks reported), doses were increased up to 380 μg/kg twice per day. The primary endpoint was the mean sBA change during the RWD in participants with at least 50% sBA reduction by week 18. Cholestastic pruritus was assessed using observer-rated, patient-rated, and clinician-rated 0–4 scales. The safety population was defined as all participants who had received at least one dose of maralixibat. This trial was registered with ClinicalTrials.gov, NCT02160782, and is closed to recruitment. Between Oct 28, 2014, and Aug 14, 2015, 31 participants (mean age 5·4 years [SD 4·25]) were enrolled and 28 analysed at week 48. Of the 29 participants who entered the randomised drug withdrawal period, ten (34%) were female and 19 (66%) were male. In the RWD, participants switched to placebo had significant increases in sBA (94 μmol/L, 95% CI 23 to 164) and pruritus (1·7 points, 95% CI 1·2 to 2·2), whereas participants who continued maralixibat maintained treatment effect. This study met the primary endpoint (least square mean difference –117 μmol/L, 95% CI –232 to –2). From baseline to week 48, sBA (–96 μmol/L, –162 to –31) and pruritus (–1·6 pts, –2·1 to –1·1) improved. In participants who continued to week 204 (n=15) all improvements were maintained. Maralixibat was generally safe and well tolerated throughout. The most frequent adverse events were gastrointestinal related. Most adverse events were self-limiting in nature and mild-to-moderate in severity. In children with Alagille syndrome, maralixibat is, to our knowledge, the first agent to show durable and clinically meaningful improvements in cholestasis. Maralixibat might represent a new treatment paradigm for chronic cholestasis in Alagille syndrome. Mirum Pharmaceuticals.